Developing Picture Storybook Learning Media in Terms of Students' Critical and Creative Thinking Skills - Gunawan, Gunawan; Suhardi, Suhardi; Makawawa, Junita Cristi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
Students' critical and creative thinking skills are important in developing elementary school student's knowledge. However, many still found that elementary school students critical and creative thinking skills are still low. This condition is caused by learning that has not been able to facilitate the learning characteristics of elementary school students, especially in terms of the use of learning media in elementary schools. This study aims to develop picture storybook learning media regarding fifth-grade students' critical and creative thinking skills at SD Cluster IV Sintang. The method employed in this study was research and development of the Borg & Gall model with ten stages consisting of: 1) research and information gathering, 2) planning, 3) initial product development, 4) initial field testing, 5) major product revision, 6) main product testing, 7) operational product revision, 8) operational field testing, 9) final product revision, and 10) dissemination and implementation. Data were collected utilizing interview techniques, expert validation, teacher and student response questionnaires, and critical and creative thinking skill test instruments. The results of this study indicate that the development of picture storybook learning media meets the aspects of quality, practicality, and product effectiveness in terms of the critical and creative thinking skills of fifth-grade elementary school students.